Tinjauan Sistematis: Gambaran Kesehatan Mental Perawat yang Menangani Pasien Covid-19 - Ernestine Oktaviana Yuniswara (Journal An-Nafs: Kajian Penelitian Psikologi, 2021)
Nurses hold pivotal role during COVID-19 pandemic through providing care toward the infected patients. Various pressures experienced by the nurses while working with COVID-19 patients affected their mental health states. This systematic review attempted to describe the mental health state of nurses who specifically work with COVID-19 patients. Five journals published in 2020 by international publishers were assessed for the methodological rigorousness including the title and its abstract, introduction and research aims, method and data, sampling, data analysis, ethics and bias, results, transferability, as well as the implications and usefulness. Through rigorous review of five studies using PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) protocol, the mental health state of the nurses caring for patients diagnosed with COVID-19 patients can be inferred from emotional, cognitive and behavior components, with mental health aspects such as anxiety, anger, fear, sadness, distress, happiness, optimism and germ aversion. Findings from this systematic review can be further developed as a more elaborate research using psychological variables found in nurses caring for COVID-19 patients